Oral Pigmentation - A Review - Nalin Kumar; T R Saraswathi (Wolters Kluwer Medknow Publications, 2003)
Pigments are defined as substances occuring in living matter, which absorb visible light. They are substances, which possess colour of thier own in their natural state. Pigments differ in origin, chemical constitution and their biological significance. Variations in the normal oral pigmentation can occur due to genetic factors, hormonal imbalances and side effects of drugs. Several endogenous and exogenous factors, local & systemic may cause dermal and mucosal pigmentation alterations. This article reviews the literature of physiological oral pigmentation in different populations and the various causes of pathologic oral hyperpigmentation.